The protein phosphatase subunit PP2A‐B′γ is required to suppress day length‐dependent pathogenesis responses triggered by intracellular oxidative stress. Issue 1 (2nd December 2013) - Li, Shengchun; Mhamdi, Amna; Trotta, Andrea; Kangasjärvi, Saijaliisa; Noctor, Graham
Summary: Oxidative stress responses are influenced by growth day length, but little is known about how this occurs. A combined reverse genetics, metabolomics and proteomics approach was used to address this question in Arabidopsis thaliana . A catalase‐deficient mutant ( cat2 ), in which intracellular oxidative stress drives pathogenesis‐related responses in a day length‐dependent manner, was crossed with a knockdown mutant for a specific type 2A protein phosphatase subunit ( pp2a‐b′ γ). In long days (LD), the pp2a‐b′ γ mutation reinforced cat2 ‐triggered pathogenesis responses. In short days (SD), conditions in which pathogenesis‐related responses were not activated in cat2, the additional presence of the pp2a‐b′ γ mutation allowed lesion formation, PATHOGENESIS‐RELATED GENE1 ( PR1 ) induction, salicylic acid (SA) and phytoalexin accumulation and the establishment of metabolite profiles that were otherwise observed in cat2 only in LD. Lesion formation in cat2 pp2a‐b′ γ in SD was genetically dependent on SA synthesis, and was associated with decreased PHYTOCHROME A transcripts. Phosphoproteomic analyses revealed that several potential protein targets accumulated in the double mutant, including recognized players in pathogenesis and key enzymes of primary metabolism. We conclude that the cat2 and pp2a‐b′ γ mutations interact synergistically, and that PP2A‐B′γ is an important player in controlling day length‐dependent responses to intracellular oxidative stress, possibly through phytochrome‐linked pathways.